Diagnosis of Intracranial Germ Cell Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators from the Massachusetts General Hospital, Boston, studied the manifestations and time to diagnosis of 70 children with germ cell tumors (GCTs) treated between 1998 and 2012.